2016
DOI: 10.1021/acs.iecr.6b02479
|View full text |Cite
|
Sign up to set email alerts
|

Hierarchical Pore Structures and High ZIF-8 Loading on Matrimid Electrospun Fibers by Additive Removal from a Blended Polymer Precursor

Abstract: A novel method for increasing the effective nanoparticle loading in electrospun fibers is presented involving the electrospinning of polymer blends with suspended ZIF-8 crystals. Initially, varying ratios of Matrimid 5218 and poly-(ethylene oxide) (PEO) are electrospun, followed by methanol washes to remove PEO to form porous Matrimid nanofibers. After an optimum surface area is found from the ratio of 1:1 Matrimid:PEO by weight, the metal-organic-framework ZIF-8 is suspended in the polymer blend and electrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 29 publications
0
25
0
1
Order By: Relevance
“…Electrospun fibers were fabricated using an apparatus described previously . 1:1:0.25 MAT:PEO:ZIF‐8 and 1:1:2 MAT:PEO:ZIF‐8 were prepared in a previous study by the same manner and more details and characterization are shown there …”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…Electrospun fibers were fabricated using an apparatus described previously . 1:1:0.25 MAT:PEO:ZIF‐8 and 1:1:2 MAT:PEO:ZIF‐8 were prepared in a previous study by the same manner and more details and characterization are shown there …”
Section: Experimental Materials and Methodsmentioning
confidence: 99%
“…To form porous electrospun fiber scaffolds for the crushed IER, a SPAR technique developed by our group is used . A solution containing 400 mg crushed resin is suspended in a 10 mL dimethylformamide solution containing a 400 mg polystyrene and 400 mg poly(ethylene oxide) (MV = 400,000, Sigma‐Aldrich) blend.…”
Section: Methodsmentioning
confidence: 99%
“…One shortcoming of dense electrospun fibers are the fact that many of the particles become buried in the polymer phase and inaccessible to the fluid stream causing a lower sorption capacity . To overcome this hurdle, we have developed a solvothermal polymeric additive removal (SPAR) technique that creates porous electrospun fibers to remedy this issue . This design strategy has already been replicated by Qin and coworkers for antibiotic removal in which it was demonstrated that immobilizing a catalyst in porous fiber that nears the performance of freestanding catalyst with the benefit of immobilization and reusability …”
Section: Introductionmentioning
confidence: 99%
“…This route can overcome some of the drawbacks of the direct electrospinning route discussed in Section 2.1, such as poor dispersion of MOF particles in the polymers, blockage of MOF pores, or reduced mechanical properties, such as high brittleness due to MOF loading. [71] Copyright 2017, American Chemical Society. For this purpose, a variety of processing methods or their Adv.…”
Section: Surface Decoration Of Polymer Nanofibers With Mofsmentioning
confidence: 99%
“…c) N 2 isotherms for different ratios of Mat:PEO:ZIF‐8 in the “as‐synthesized” nanofibers and after PEO removal (“washed”). Reproduced with permission . Copyright 2017, American Chemical Society.…”
Section: Routes For the Structuring Of Mof Nanofiber Architecturesmentioning
confidence: 99%